PREFERENCES FOR CARE NEAR THE END OF LIFE AMONG UNDERGRADUATE NURSING STUDENTS. (16th November 2018) - Cheon, J
Abstract: As advanced medical care has resulted in the unintended consequence of prolonging deaths, there is a growing interest in the advance directives and the preferences for end-of-life care in undergraduate nursing students who will work as a nurse near patients who are dying. The purposes of this study were (1) to examine the level of the preferences for autonomous decision-making, decision-making by healthcare professionals, spirituality, family, and pain control, and (2) to identify factors associated with the preferences for care near the end-of-life among undergraduate nursing students in South Korea. A cross-sectional descriptive research design was used. Data were collected from December 2017 to February 2018 using a structured questionnaire. Multivariable linear regression was used to identify factors associated with the preferences for care near the end-of-life. This study included 217 undergraduate nursing students with an average age of 21.0 ± 1.6 years old. Pain control was the most preferred dimension while decision-making by health care professionals was the least preferred dimension. Preference for autonomous decision-making was associated with grade, having biomedical education, and attitude toward death and life-sustaining treatments. Preference for decision-making by healthcare professionals was related to religion. Factors related to preference for spirituality were grade, religion, and satisfaction in nursing major. Preference for pain control was associated with grade, experience to observe dying patients, bad health status of participants, and attitude toward death and life-sustaining treatments. Further studies should develop educational intervention programs, which change attitude toward death and life-sustaining treatments positively and prepare nursing students for end-of-life care.